Iluminação em salas de aula do Centro de Tecnologia da Universidade Federal da Paraíba: um estudo de caso - Lucena, Mariana Caldas Melo (2015)
Educational issues have triggered much discussion in Brazil, where it has been put in question the quality of student performance, especially in public educational settings. In this research the issues related to visual comfort will be studied in order to characterize the performance of complementary natural and artificial lighting, aiming to evaluate the quantitative aspects (autonomy of natural light, daylight factor and static luminance), qualitative (uniformity and light output) identify factors that may contribute to or interfere with the lighting performance and assess the potential for reducing energy consumption in light of the availability of natural light in the classrooms of the Federal University of Paraiba Technology Center. The method adopted for the analysis of natural light behavior was the computer simulation, in which dynamic parameters analyzed were: Daylight factor and autonomy of natural light and the illuminance of artificial light as static parameter. From this, the surroundings were divided into zones of different levels of illumination, so that it was possible to identify where there is greatest need for additional artificial lighting use. To quantify the reduction potencial of the power consumption of the systems in relation to the proposed from the availability of light each environment studied were simulated in Daysim. Concluding that in all classrooms studied natural light does not have enough autonomy to achieve the illuminance levels recommended by the standard for educational environments, thus requiring an electrical lighting system that complements the light deficit, ie a system integrated natural light and artificial supplement.